A new burst error correcting method for Reed-Solomon codes based on composite parity-check matrices. (27th September 2022) - Pak, Song Chol; Yu, Nam Chol
This paper presents the construction method of composite parity-check (CPC) matrices and a new burst error correcting method for ( n, k ) Reed-Solomon (RS) codes based on CPC matrices. The proposed method is capable of finding burst error locations by only locations of symbol 0s of syndromes computed by CPC matrices and evaluating the corresponding error magnitudes using CPC matrices. The simulation results show that the proposed method can correct burst errors for the codes with the rate less than about 0.75 with lower complexity and correct burst errors of length up to n - k - 1 and burst erasures of length up to n - k .